Update on Thrombosis Risk in Patients with Cancer: Focus on Novel Anticancer Immunotherapies - Moik, Florian; Riedl, Jakob M.; Englisch, Cornelia; Ay, Cihan (Hämostaseologie, 2024)
Thromboembolic complications, including venous thromboembolism (VTE) and arterial thromboembolism (ATE), increase mortality and morbidity, and delay treatment in patients with cancer. Therefore, an increased understanding of underlying risk profiles, the identification of risk factors and predictive biomarkers, and ultimately the development of specific cardiovascular prevention strategies in patients with cancer is needed. Medical anticancer therapies have undergone a remarkable development in recent years with the advent of targeted and immunotherapeutic treatment options, including immune checkpoint inhibitors (ICI), chimeric antigen receptor (CAR) T-cell therapies and bispecific T-cell engagers (BiTEs). These developments have important implications for the accompanied risk of thromboembolic events in patients with cancer. First, the increased use of these highly effective therapies renders a growing proportion of patients with cancer at risk of thromboembolic events for a prolonged risk period due to an increase in patient survival despite advanced cancer stages. Second, potential direct cardiovascular toxicity and prothrombotic effect of novel anticancer immunotherapies are a matter of ongoing debate, with emerging reports suggesting a relevant risk of VTE and ATE associated with ICI, and relevant dysregulations of hemostasis in the frequently observed cytokine-release syndrome associated with BiTEs and CAR T-cell therapy. The aim of the present narrative review is to summarize the implications of the emerging use of anticancer immunotherapy for thromboembolic events in patients with cancer, and to provide an overview of available data on the rates and risk factors for VTE and ATE associated with ICI, CAR T-cell therapy, and BiTEs.
Keywords: cancer; venous thrombosis; arterial thrombosis; immunotherapy